Wind Characteristics Influencing Wind Energy. - E, P Chiang; Bawadi, M A; Aswatha Narayana, P A; Zainal, Z.A.; Seetharamu, K N (2003)
Usually the wind speed for a particular site is given at a standard reference height of 10 m. However, in the context of wind turbines, the hub height is a natural choice for estimating the power potential.